Understanding the Nature of Collapsed Subsurface karsts: Analogues from the Tropical Karst Regions - Chow , Weng Sum (2012)
Karst is a distinctive landform that results from the dissolution of carbonate rocks, and the dissolutional process is considered to be an important geologic phenomenon that may lead to the formation of karst reservoirs. The process of burial, compaction and diagenesis is believed to transform subaerial multiple karst caves into coalesced collapsed paleocave systems, but it is hypothesized that large passage caves of tropical karst regions can be evidence for the existence of large scale collapsed single cavern. In order to comprehend the mechanism of formation and dimensional increment after burial, a tropical karst cave was surveyed and world largest passage caves were considered. It is inferred that, not only deep burial of paleocave systems that result interconnected fractures and coalesced breccias, rather such phenomenon can be manifested if large cave passages are subjected to burial. Moreover, because of the presence of immense speleothem deposits that typify tropical karst areas, we suggest that additional cave facies, i.e. massive to slightly fractured speleothems, to be included in the pre-existing paleocave facies classification